Pemanfaatan Limbah Marmer Sebagai Agregat Dalam Campuran AC-BC - Windra Tandi Payung; Alpius; Elizabeth (Paulus Civil Engineering Journal, 2023)
Marble waste comes from the rest of unused marble stone processing. To reduce marble waste, it is necessary to innovate to use marble waste as a substitute for aggregate on the pavement layer. The purpose of this study was to determine the influence of materail characteristics in the AC-BC mixture with the marshall method and the use of marble waste PT. Great Marble Mountain. From laboratory tests for material characteristics, namely aggregate, asphalt and cement, test results are obtained to meet the provisions of Highways. For the composition of the AC-BC mixture, 38.05% coarse aggregate, 50.70% fine aggregate and 6.25% cement were obtained. According to the calculation results, the results of VIM, Stability, VMA, VFB, and Flow tests and SMS have passed the provisions of Highways Specification.